2018
DOI: 10.1002/micr.30358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long‐term functional donor‐site morbidity after deep circumflex iliac crest artery bone flap harvest

Abstract: Functional donor site morbidity after DCIA harvesting can be expected to be low in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…In their study, there were no impairments of daily life activities in the long term, with a low impact of decreased joint mobility in patients' daily life. 50 In our series, the ASIS was always preserved. Due to the accurate CAD/CAM planning and using the 3D guides and models, precise amounts of iliac crest are used, making it possible to easily preserve the ASIS.…”
Section: Preservation Of the Asismentioning
confidence: 57%
“…In their study, there were no impairments of daily life activities in the long term, with a low impact of decreased joint mobility in patients' daily life. 50 In our series, the ASIS was always preserved. Due to the accurate CAD/CAM planning and using the 3D guides and models, precise amounts of iliac crest are used, making it possible to easily preserve the ASIS.…”
Section: Preservation Of the Asismentioning
confidence: 57%
“…This can be supported by a study by Rendenbach et al who reported that harvest of DCIA flaps may lead to restricted mobility of the hip joint in all the three planes secondary to the muscle guarding. 21 Hence it is essential to restrict the quantum of graft harvest to avoid untoward complications in paediatric population. Restricting the quantum of graft harvest to 50% of the volume available by preoperative CT evaluation, respecting the anatomical constraints of the Pediatric hip bone, maintaining the integrity of the cortical shell are essential to avoid these untoward complications.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies showed the high incidence of chronic pain in up to one third of iliac crest bone graft patients (Ropars et al, ; Skeppholm & Olerud, ). Rendenbach et al () recently analyzed the donor site morbidity after deep circumflex iliac crest artery bone flap harvest in 14 patients. The found a reduction in mobility of the hip joint and the lumbar spine, along with restrictions in standing up from a bent position and sensory deficits.…”
Section: Discussionmentioning
confidence: 99%